Fragility of Bridge Columns under Vehicle Impact Using Risk Analysis - Kyeongjin Kim; Jaeha Lee (Advances in Civil Engineering)
In this study, risk analysis was conducted to evaluate the vulnerability of bridge columns to vehicle impact. A three-step risk analysis procedure was used. The first step involved a Preliminary Risk Analysis (PRA), which was an initial screening step to determine whether a bridge column requires second-step analysis or not. The second step was a Simplified Risk Analysis (SRA), which involved determining the level of risk (low, moderate, or high) for a bridge column. The third step comprised a Detailed Risk Analysis (DRA). Computer simulation was based on the results of SRA. In this study, the risk level of 8,267 bridges in South Korea was evaluated, and a resulting total of 58 bridge columns in the Risk Level High (RLH) category were selected as a result of SRA. These bridge columns were classified into five types based on their slenderness ratio. Using these five types of bridge column, DRA was conducted. As expected, larger deformations of the bridge column were observed if the vehicle velocity and slenderness ratio were both increased. Using the bridge columns in the categories of response high and response moderate under vehicle impact, fragility curves were proposed using statistical data of material strength and the few results of the numerical analysis.